2019
DOI: 10.1016/j.heliyon.2019.e02372
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical characterization of dual action liposomal formulations: anticancer and antimicrobial

Abstract: Background: Cancer till date remains one of the world's most life threatening disease accompanied by risk of secondary infections. Therefore formulations carrying anticancer drugs which can also decrease the risk of secondary infection are inevitable. Chemotherapeutic drug doxorubicin along with flavonoids quercetin and epigallocatechin gallate (EGCG) is simultaneously loaded on liposomal formulation exploiting the amphiphilic property of the liposomes. Results: Atomic force microscope imaging reveal the size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…Similar explanation of dark and light area were explained in the previous studies (Ruozi et al, 2011 ;Topal et al, 2018). In one of the previous study the flattening of liposome was observed which is thought to be considered because of their high surface density preventing the tip from direct contact with the liposomal surface (Das et al, 2019). Moreover, AFM was being used in current study to examine the lipid bilayers and to observe the significant differences of liposomes and ciprofloxacin encapsulated liposomes.…”
Section: Characterization Of Liposomes and Ciprofloxacin Encapsulated...supporting
confidence: 75%
“…Similar explanation of dark and light area were explained in the previous studies (Ruozi et al, 2011 ;Topal et al, 2018). In one of the previous study the flattening of liposome was observed which is thought to be considered because of their high surface density preventing the tip from direct contact with the liposomal surface (Das et al, 2019). Moreover, AFM was being used in current study to examine the lipid bilayers and to observe the significant differences of liposomes and ciprofloxacin encapsulated liposomes.…”
Section: Characterization Of Liposomes and Ciprofloxacin Encapsulated...supporting
confidence: 75%
“…Liposome co‐loading resveratrol and curcumin exhibited greater EE (80.42 %) compared to single loaded PCs (resveratrol loaded liposome: 59.46 % and curcumin loaded liposome: 68.16 %). Das et al [60] . also obtained a high EE of 96.8 % and 98 % for quercetin and EGCE, respectively, using the co‐encapsulation method.…”
Section: Encapsulation Efficacymentioning
confidence: 94%
“…also attempted a similar co‐encapsulation of curcumin and resveratrol to enhance the stability, antioxidant efficacy, and encapsulation efficacy of the system. Again, Das et al [60] . have simultaneously loaded polyphenol quercetin and EGCG along with anticancer drug doxorubicin to enhance the effectiveness of the total system.…”
Section: Methodology Of Liposomal Encapsulation Of Pcsmentioning
confidence: 99%
See 2 more Smart Citations